IP-based high-available mass network storage system - HAN De-zhi1; YU Shun-zheng1 (Tongxin xuebao)
An IP-based high-available mass network storage system（MNSS） was introduced,featured by the following advantages: firstly,it integrates multi-NAS and SAN with OSD through a unified multi-protocol file system（UMPFS）,with greater capacity and better scalability than each of them;secondly,it simultaneously serves both the file I/O and the block I/O by an iSCSI module,with all the advantages of a NAS and a SAN;thirdly,with an autonomic storage agency（ASA）,the MNSS provide two kinds of data channels,i.e.,a server channel and a high-speed network-attached channel,by which the I/O performance is improved and server bottlenecks are reduced;fourthly,high availability is attained by way of a high-available file system.In addition,in the experiment concerned,the MNSS has proved to be a network storage system with great capacity producing an ultra-high-throughput for both the file I/O and the block I/O,characterized by better performance,scalability,availability and cost performance,etc.when compared with those systems already on the market.